2021
DOI: 10.3390/ijms22179485
|View full text |Cite
|
Sign up to set email alerts
|

Effects of β-Phenylethylamine on Psychomotor, Rewarding, and Reinforcing Behaviors and Affective State: The Role of Dopamine D1 Receptors

Abstract: Beta-phenylethylamine (β-PEA) is a well-known and widespread endogenous neuroactive trace amine found throughout the central nervous system in humans. In this study, we demonstrated the effects of β-PEA on psychomotor, rewarding, and reinforcing behaviors and affective state using the open-field test, conditioned place preference (CPP), self-administration, and ultrasonic vocalizations (USVs) paradigms. We also investigated the role of the dopamine (DA) D1 receptor in the behavioral effects of β-PEA in rodents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 60 publications
(81 reference statements)
0
5
0
Order By: Relevance
“…Aromatic amines are among the compounds detected in the colon; 12 , 13 tryptamine, tyramine, and phenylethylamine (PEA) are typically known as the trace amines that can affect neurotransmission even in small amounts. 14 , 15 Diet and gut microbiota have been identified as sources of colonic luminal aromatic amines. Aromatic amines are found in fermented foods, 16 nuts, and citrus fruits 17 as well as in roasted coffee and cacao, where they are generated by Maillard- and Strecker reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Aromatic amines are among the compounds detected in the colon; 12 , 13 tryptamine, tyramine, and phenylethylamine (PEA) are typically known as the trace amines that can affect neurotransmission even in small amounts. 14 , 15 Diet and gut microbiota have been identified as sources of colonic luminal aromatic amines. Aromatic amines are found in fermented foods, 16 nuts, and citrus fruits 17 as well as in roasted coffee and cacao, where they are generated by Maillard- and Strecker reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Among the hydrophilic metabolites, the levels of phenylethylamine and L-tyrosine were decreased remarkably in the N-WD group. β-phenylethylamine is an endogenous neuroactive trace amine that is widespread in the human central nervous system, and previous research showed that it increased the synaptic levels of dopamine (DA) (13). L-tyrosine is a precursor of DA, and can effectively increase catecholaminergic activities, including those mediated by DA (14).…”
Section: Discussionmentioning
confidence: 99%
“…Locomotor activity test was performed as described previously. , Rats were acclimated to the open-field arena in an illuminated and sound-attenuated cubicle for three consecutive days (30 min/day). Locomotor activity was measured and recorded using a computer-based monochrome/near-infrared video camera on days 1, 4, and 7.…”
Section: Methodsmentioning
confidence: 99%